Contemporary writing: animation cinema - de Andrade, María de Fátima Ramos; Aparício, Ana Silvia Moço (Universidad Pedagógica y Tecnológica de Colombia, 2019)
On the basis of a reflection on the concepts of language, we aim to discuss the concept of contemporary writing. In order to show how this writing is constituted, we present a synthesis of the history of animation cinema. The historicization of a certain representation system is not only an opportunity to illustrate some movements in the dissemination of culture, but also an exercise to understand how this culture has undergone transformations. It becomes apparent how these systems that men themselves “created” have been transformed.